EMAS SEBAGAI LINDUNG-NILAI INFLASI - Tomy G. Soemapradja (Bina Nusantara University, 2012)
One of the factors that can reduce the value of assets and investments is inflation. Inflation is a systemic risk that cannot be avoided even it is performed portfolio management. Nevertheless, it could still be pursued with inflation hedging, ie by combining gold investments in a portfolio investor.